SAVAVALDŽIAVIMO NUSIKALTIMO IR CIVILINIŲ TEISIŲ SAVIGYNOS SANTYKIS - Višinskis, Gerardas (Teisė, 2015)
Straipsnyje tiriamas savavaldžiavimo nusikaltimo ir civilinių teisių savigynos santykis, jų panašumai ir skirtumai. Analizuojama savigalbos samprata, jos, savigynos ir savavaldžiavimo santykis. Nagrinėjamos savigynos įgyvendinimo sąlygos, jų pažeidimo teisiniai padariniai. The article analyses the relationship between self-willed conduct and self-defence of civil rights as well as similarities and differences of these phenomena. The article also looks into the concept of self-help, its relationship with self-defence and self-willed conduct. Conditions for self-defence and legal consequences of breaches thereof are, moreover, analyzed.